Time course of cardiac rupture after acute myocardial infarction and comparison of clinical features of different rupture types - Liang, Chendi; Wang, Xiaoxia; Yang, Peng; Zhao, Ru; Li, Li; Wang, Zhixin; Guo, Yanqing (Frontiers in Cardiovascular Medicine, 2024)
Objective: This study aimed to investigate the time course of cardiac rupture (CR) after acute myocardial infarction (AMI) and the differences among different rupture types.We retrospectively analyzed 145 patients with CR after AMI at Shanxi Cardiovascular Hospital from June 2016 to September 2022. Firstly, according to the time from onset of chest pain to CR, the patients were divided into early CR (≤24 hours) (n=61 patients) and late CR (> 24 hours) (n=75 patients) to explore the difference between early CR and late CR.Secondly, according to the type of CR, the patients were divided into free wall rupture (FWR) (n=55) and ventricular septal rupture (VSR) (n=90) to explore the difference between FWR and VSR.Results: Multivariate logistic regression analysis showed that high white blood cell count (OR=1.134, 95% CI: 1.019~1.260, P=0.021), low creatinine (OR=0.991, 95% CI: 0.982~0.999, P=0.026) were independently associated with early CR. In addition, rapid heart rate (OR=1.035, 95% CI: 1.009~1.061, P=0.009), low systolic blood pressure (OR=0.981, 95% CI: 0.962~1.000, P=0.048), and anterior myocardial infarction (OR=5.989, 95% CI: 1.978~18.136, P=0.002) were independently associated with VSR.In patients with CR, high white blood cell count and low creatinine were independently associated with early CR, rapid heart rate, low systolic blood pressure, and anterior myocardial infarction were independently associated with VSR.